A Tool, an App and a Field: Fluorescent PET Sensors, Blood Electrolyte Analysis and Molecular Logic as Products of Supramolecular Photoscience from Northern Ireland and Sri Lanka. Issue 4 (1st December 2022) - Yao, Chao‐Yi; de Silva, A. Prasanna
Abstract: The general tool of fluorescent PET (photoinduced electron transfer) sensors/switches – a molecular design principle with engineering features – is outlined, with the aid of frontier orbital energy diagrams. Fluorophores such as anthracene, 1, 3‐diaryl‐Δ 2 ‐pyrazolines and 4‐amino‐1, 8‐naphthalimides are employed within this system, alongside receptors such as amines, carboxylates, crown ethers and amino acids. This tool appealed to a multinational corporation for building a medical analyzer for electrolytes such as Na +, K +, Ca 2+ and gases like CO2, which became a commercially successful application. Finally, the tool was a springboard for chemistry to cross into computer science. The field of molecular logic can elucidate how molecules inside us handle information. Molecular examples of the simplest logic gates such as YES, NOT, OR, AND are described. A case of a human‐level computation – visual edge detection – is also included. Abstract : Serendipity, in the form of personal encounters, gave birth to the generalization of fluorescent PET (photoinduced electron transfer) sensors and to their application in the OPTI blood gas and electrolyte analyzer. The serendipitous realization that a sensor can also be operated as a switch gave birth to the field of molecular logic‐based computation, which now has contributions from chemists, molecular biologists and other life scientists.